The outcomes of secondary AML post allogeneic hematopoietic cell transplantation significantly depend on the presence of poor‐risk cytogenetic abnormalities. Issue 2 (12th March 2021) - Hassanein, Mona; Fakih, Riad El; Rasheed, Walid; Ahmed, Syed; Shaheen, Marwan; Chaudhri, Naeem; Alsharif, Fahad; Ahmed, Shad; Hanbali, Amr; AlShaibani, Alfadel; Alfraih, Feras; Alhayli, Saud; et al.
Abstract: Secondary acute myeloid leukemia (sAML) includes AML as a complication of an antecedent hematological disorder or a therapy‐related AML. Large registry‐based data identified sAML as an independent poor‐outcome type of AML post allogeneic hematopoietic cell transplantation (allo‐HCT). In our study, we tried to define factors affecting outcomes of sAML post allo‐HCT, and identify patients with sAML who may truly benefit from allo‐HCT. We retrospectively analyzed the data of 64 patients aged (14‐61 years) with sAML who received allo‐HCT between September 2010 and February 2018 at our institute. Most of the patients were transplanted from matched related donors (MRD; 54, 84.4%). Our results showed that poor‐risk cytogenetics were identified in 31 patients (48.4%), and their presence was an indicator of poor overall survival (OS) and disease‐free survival (DFS; P ‐value = .009, and .004, respectively). The cumulative incidence of chronic graft‐versus‐host disease (cGVHD) was significantly lower in sAML patients with poor‐risk cytogenetics ( P ‐value = .003) resulting in a high risk of death without cGVHD in this group of patients ( P ‐value = .02). Besides, GVHD relapse‐free survival (GRFS) analysis showed that most of our studied patients experienced either relapse or debilitating grade II‐IV cGVHD in the first 2 years post allo‐HCT. We conclude that sAML patients with poor‐risk cytogenetics have a significantly lower DFS post allo‐HCT with a high risk of death without active cGVHD.